Advances in Systems Biology - Goryanin, Igor I.; Goryachev, Andrew B.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
AEMB series
Preface -- Part 1: Multiscale biological networks: identification, modeling and analysis -- Part 2: Cellular decision making: adaptation, differentiation and death -- Part 3: Spatial and temporal dymensions of intracellular dynamics -- Part 4: Computational tools: algorithms and theoretical methods for systems biology -- Part 5: Applications of systems biology in medicine, biotechnology and pharmaceutical industry -- Index.
Keywords: Life sciences; Medicine; Bioinformatics; Biological models; Life Sciences; Systems Biology; Bioinformatics; Biomedicine general